Enhancing Capability of Tanjung Bumi Batik Sales Bangkalan Madura - Astria Hindratmo; Ong Andre Wahyu Riyanto (Kontribusia : Research Dissemination for Community Development, 2019)
Madura Island besides producing salt, it turns out that it is also the producer of the craft written batik. One of the regions that have batik-producing SMEs is in Tanjung Bumi Bangkalan Madura District. In Tanjung Bumi Subdistrict there are very many batik craftsmen with a distinctive bird motif. However, although there are many batik SMEs, there are also many craftsmen who close their businesses due to having several problems in their business. One of the problems is not having a good marketing concept and not being able to utilize information technology through the internet in marketing activities. This can be seen from the sales activities that still rely on shops and also just waiting for suppliers or buyers from outside the city such as from Surabaya. With the competition of batik sales outside the city, such as Surabaya, causing the number of buyers from Surabaya is currently decreasing. The decline finally drastically impacted the decline in sales of Tanjung Bumi written batik. The purpose of this activity is to provide knowledge and insight into designing 4P marketing mix concepts (Product, Price, Place, Promotion) and determining STP (Segmentation, Targeting, Positioning) and making SME partners begin to take advantage of internet technology for online advertising. The method used in this activity is to train to create marketing concepts and train the use of online media and social media to advertise. The result of this activity is that partners have the knowledge of designing marketing concepts and are able to innovate in marketing activities using information technology with the internet on social media